PENGARUH KEPUASAN KARIR DAN JOB INSECURITY TERHADAP TURNOVER INTENTION DENGAN MEDIASI KOMITMEN ORGANISASI PADA PEGAWAI RS ISLAM PURWOKERTO - Nisa Hidayah; Hengky Widhiandono; Akhmad Darmawan; Restu Frida Utami (Politeknik Negeri Ambon, 2026)
Introduction: This study aimed to examine the influence of career satisfaction and job insecurity on turnover intention, with organizational commitment serving as a mediating variable, among employees of Purwokerto Islamic Hospital.Methods: A quantitative approach was employed involving a population of 130 employees from various departments at Purwokerto Islamic Hospital, including nurses, pharmacists, PPJA (nurses in charge of care), ward heads or coordinators, laundry staff, cleaning service staff, medical records staff, and security guards. Data were collected using a questionnaire, and analyses were performed using SmartPLS version 3.Results: The research findings indicate that career satisfaction has a positive but insignificant effect on both organizational commitment and turnover intention. In contrast, job insecurity was found to have a positive and significant effect on turnover intention and organizational commitment. Organizational commitment was also shown to have a positive and significant effect on turnover intention. Additionally, the results indicated that organizational commitment did not mediate the relationship between career satisfaction and turnover intention, but did mediate the relationship between job insecurity and turnover intention. Overall, these findings highlight the critical roles of job insecurity and organizational commitment in efforts to reduce employee turnover rates. Keywords: Career Satisfaction, Job Insecurity, Organizational Commitment, SmartPLS, Turnover Intention